KEWENANGAN PENYIDIK MILITER TERHADAP TINDAK PIDANA PENCUCIAN UANG DALAM PERADILAN MILITER DI INDONESIA - Zahwa Rizqi Laurina (2022)
The crime of money laundering is a crime classified as a white collar crime. Money laundering (money laundering) is an activity carried out using or carrying put other activities resulting from criminal acts carried out by individuals or organizations that commit corruption, narcotics trafficking and other acts of poaching. Simple money as a result of ways or processes to convert money obtained from illegal sources so that it can be considered as halal. Related to the handling of criminal acts of money committed by TNI soldiers, the method of settlement is the same as other follow-up relted to the process of investigation, prosecution and examination of trials and the implementation of court decisions. Article 74 of the TPPU Law does not explicitly state that investigations can be carried out by the Military Policy, which regulates only six (6) investigative institusions. While Military Broadcasting regulates Law 31 of 1997 by completing Money Laundering Crimes commited by TNI soldiers.This research wa conducted to analyze and analyze the POM investigators to carry out investigations on TNI Soldiers who commit Money Laundering. From the results of research, it shows that the research on the unification of money laundering crimes against TNI soldiers is still among those who oppose the TPPU Law, limited to formulating six investigative institusions without including Military court investigator, namely Ankum, Military Police, and Military Oditur. The results of the study concluded that Military Court investigators have the authority to conduct an investigation of the TPPU conducted by TNI Soldiers.